Factors influencing career mobility decisions and career expectations among the 1980–2000 workforce in Vietnam: The role of career orientation in lower secondary education - Huong, Nguyen Thi; Minh, Thanh Anh; Phuong, Mai Thi; Trang, Ho Huyen (Edelweiss Applied Science and Technology, 2026)
This study examines the long-term impacts of lower secondary school career orientation experiences on the adult career mobility decisions and career satisfaction of the Vietnamese workforce born between 1980 and 2000. Employing a quantitative survey design with a sample of 1,059 working individuals, the research integrates Savickas’s Career Construction Theory, Human Capital Theory, Boundaryless Career Theory, and the Systems Theory Framework to evaluate structural and individual career determinants. Descriptive results indicate an overreliance on theoretical career instruction (Mean = 3.43) and minimal practical exposure (Mean < 3.00 for facility field trips). Inferential statistical analyses demonstrate that while early practical exploration frequencies do not significantly prevent adult job-hopping (p = 0.591), and adult job-matching with childhood preferences does not dictate long-term satisfaction (p > 0.05), the early formation of a distinct vocational interest during lower secondary education acts as a critical anchor, triggering significantly higher career satisfaction across all dimensions in adulthood (Mean = 4.00 vs. 3.29, p = 0.000). For job-changers (n = 213), career insecurity (28.87%) and workplace conflicts (25.09%) were primary push factors. Developing distinct early vocational interests acts as a vital psychological anchor for long-term career fulfillment. Results emphasize transitioning from theory-heavy guidance toward structured, technology-driven, and personalized career counseling models.